Structure and Size Optimization of Quadruped Robot Single Leg Structure for Trot Gait - Yuegang Tan; Xinyu Dong; Tianqi Hu (Jixie chuandong)
The single-leg of quadruped robot is the main support unit of the whole robot，and it is also the motion unit of the bottom layer of quadruped robot. Therefore，the design of single-leg will directly affect the movement ability of quadruped robot. Aiming at the Trot gait characteristics of quadruped robot，a new type of single-leg structure adapted to Trot gait is designed，the structure of the new single-leg is optimized from the perspective of size optimization. The numerical results show that the optimized single-leg improves significantly in two aspects，such as increasing the working space and reducing the driving torque，which can be integrated into the whole quadruped robot system as the bottom structure，and also provide some references for the whole quadruped robot structure design.